The Effects of the Psychological Contract Among Professional Employees Working in Non-Professional Organizations - Paillé, Pascal; Raineri, Nicolas; Valeau, Patrick (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
Few researchers have sought to examine the consequences of psychological contract breach in the particular case of professional employees working for nonprofessional organizations. To increase our understanding, the purpose of this article was to test an original research model encompassing psychological contract breach, psychological contract violation, perceived organizational support, organizational and professional commitment, and intention to leave the organization. A study was conducted among a sample of 329 professional employees working in nonprofessional organizations. As predicted, this research shows a positive relationship between psychological contract breach and psychological contract violation, a negative relationship between breach and organizational commitment, and a negative relationship between organizational commitment and the intention to leave the organization. However, contrary to expectations, the results indicated that perceived organizational support has no moderating effect on the relationship between breach and violation. This finding does not confirm previous findings from the study by Suazo and Stone-Romero (2011). This unexpected result led to testing a different combination between perceived organizational support and PC-breach and PC-violation, which is documented in the literature on nonprofessional employees. Thus, in accordance with previous results by Suazo (2009), the data from our research indicate that the relationship between PC breach and perceived organizational support is mediated by PC violation. This alternative research model suggests testing a long mediation process by which the breach influences the intention to leave the organization via the violation, the perceived organizational support, and professional and organizational commitment. This long mediation process has been confirmed by our data. Finally, the results of this research suggest that when working in a non-professional context, professional employees tend to react to breaches of the psychological contract in a similar way to non-professional employees.